2010
DOI: 10.1007/s11258-010-9729-6
|View full text |Cite
|
Sign up to set email alerts
|

Separation of grassland litter and ecosite influences on seasonal soil moisture and plant growth dynamics

Abstract: While plant litter is known to regulate soil moisture, little is known about the extent to which litter impacts moisture over and above the physical environment (i.e., ecosite) throughout the growing season, particularly in cool-temperate grasslands where moisture is considered less limiting for plant growth. In this study, we examined the relative impact of litter and ecosite on growing season soil moisture in a northern rough fescue (Festuca hallii) grassland. We also examined the relationship between litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 58 publications
(86 reference statements)
1
32
1
Order By: Relevance
“…It has been shown that litter reduces evaporation from the soil and the temperature amplitude (Deutsch et al . ; Loydi et al . ), which have positive effects during dry periods, in areas of high insolation or with high temperatures (Facelli & Pickett ; Loydi et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that litter reduces evaporation from the soil and the temperature amplitude (Deutsch et al . ; Loydi et al . ), which have positive effects during dry periods, in areas of high insolation or with high temperatures (Facelli & Pickett ; Loydi et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, effects of litter also depend on litter amount (Gross ; Wilsey & Polley ). Moderate litter amounts may support vegetation development by improving microsite conditions, that is, attenuating extremes in moisture and temperature (Fowler ; Jensen & Gutekunst ; Eckstein & Donath ; Deutsch, Bork & Willms ; Eckstein et al . ), and thus facilitating the performance of living vegetation (Brooker et al .…”
Section: Introductionmentioning
confidence: 99%
“…Litter accumulation can alter species composition (Amatangelo, Dukes, & Field, 2008;Letts, Lamb, Mischkolz, & Romo, 2015;Weltzin et al, 2005), decrease species richness and evenness (Amatangelo et al, 2008;Foster & Gross, 1998), and increase the cover of some species (Weltzin et al, 2005). Some studies report that litter accumulation increased community ANPP (Deutsch, Bork, & Willms, 2010a;Wang et al, 2011), but some studies found the opposite (Kelemen, Török, Valkó, Miglécz, & Tóthmérész, 2013). Some studies report that litter accumulation increased community ANPP (Deutsch, Bork, & Willms, 2010a;Wang et al, 2011), but some studies found the opposite (Kelemen, Török, Valkó, Miglécz, & Tóthmérész, 2013).…”
mentioning
confidence: 99%
“…Additionally, litter accumulation may delay the freezing of soil in winter and thawing in spring (Facelli & Pickett, 1991a). Decreased soil temperature also indirectly improves soil moisture (Deutsch et al, 2010a). Litter can directly increase soil moisture by reducing water evaporation (Deutsch, Bork, & Willms, 2010b).…”
mentioning
confidence: 99%
See 1 more Smart Citation